THE INFLUENCE OF GAME MECHANICS AND IN-GAME CHARACTER IN MASSIVELY MULTIPLAYER ONLINE GAMES (MMOG) TO TEAMWORK PERFORMANCE OF STUDENTS IN THE INTERNATIONAL PROGRAM IN ACCOUNTING, DEPARTMENT OF ACCOUNTING, FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITY - Dinata, Reyhan Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research examines the influence of game mechanics and in-game character in massively multiplayer online game to teamwork performanceÂ ofÂ students in the International Program in Accounting, Department of Accounting, Faculty of Economics and Business, University of Brawijaya. This research used quantitative method. Sampling method used in this research was purposive sampling which resulted in 52 students who play online games. Data was gathered from the respondents using questionnaire. Answers from respondents were scored based on Likert Scale. Hypothesis was tested using t Test and F test. Partially, this research explains that game mechanics significantly affect teamwork while in-game character does not. Simultaneously, both independent variable affect teamwork. These results show that game mechanics and in-game character in massively multiplayer online games give significant influence to students who play them and that behaviour affects positively in students real life and future. Keywords : Teamwork performance, In- Game Character, Game Mechanics, MMOG